2013
DOI: 10.1371/journal.pone.0065813
|View full text |Cite
|
Sign up to set email alerts
|

Dark Carbon Fixation: An Important Process in Lake Sediments

Abstract: Close to redox boundaries, dark carbon fixation by chemoautotrophic bacteria may be a large contributor to overall carbon fixation. Still, little is known about the relative importance of this process in lake systems, in spite the potentially high chemoautotrophic potential of lake sediments. We compared rates of dark carbon fixation, bacterial production and oxygen consumption in sediments from four Swedish boreal and seven tropical Brazilian lakes. Rates were highly variable and dark carbon fixation amounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 49 publications
4
38
1
Order By: Relevance
“…1, (18)). While these are point measurements and should be taken with caution, they are well in line with dark carbon fixation values measured from lake sediments (19).…”
Section: Resultssupporting
confidence: 85%
“…1, (18)). While these are point measurements and should be taken with caution, they are well in line with dark carbon fixation values measured from lake sediments (19).…”
Section: Resultssupporting
confidence: 85%
“…It should be noted that two of these studies are based on laboratory incubations with homogenized sediments [12], [15]. Thomsen and Kristensen [12] reported maximum rates of approximately 0.35 µmol C cm −3 d −1 (averaged over the same depth as in the present study) similar to site ZK, whereas rates found by Enoksson and Samuelsson [13] and Lenk et al [14] are lower at about 0.12 µmol C cm −3 d −1 .…”
Section: Discussionsupporting
confidence: 49%
“…In addition, dark CO 2 fixation may contribute to low apparent RQ values. Even though dark carbon fixation has been shown to correspond to 3–15% of the sediment O 2 consumption in four Swedish lakes (Santoro et al, ), it remains unknown in how far chemoautotrophic CO 2 fixation may have contributed to the temperature dependence of apparent RQ observed in the study lakes.…”
Section: Discussionmentioning
confidence: 90%